Ferroelectric‐nanocrack Device: Ferroelectric‐Nanocrack Switches for Memory and Complementary Logic with Zero Off‐current and Low Operating Voltage (Adv. Electron. Mater. 6/2021). (10th June 2021) - Guo, Zhe; Guan, Yaodong; Luo, Qiang; Hong, Jeongmin; You, Long
Abstract : An emerging ferroelectric‐nanocrack device with excellent electrical performance, even at scaled dimensions, is demonstrated in article 2100023 by Long You and co‐workers. Such device can condense the memory and logic functions into a single device level, offering a new energy‐efficient hardware platform for logic‐in‐memory applications.